Community-acquired pneumonia. Issue 10303 (4th September 2021) - Aliberti, Stefano; Dela Cruz, Charles S; Amati, Francesco; Sotgiu, Giovanni; Restrepo, Marcos I
Summary: Community-acquired pneumonia is not usually considered a high-priority problem by the public, although it is responsible for substantial mortality, with a third of patients dying within 1 year after being discharged from hospital for pneumoniae. Although up to 18% of patients with community-acquired pneumonia who were hospitalised (admitted to hospital and treated there) have at least one risk factor for immunosuppression worldwide, strong evidence on community-acquired pneumonia management in this population is scarce. Several features of clinical management for community-acquired pneumonia should be addressed to reduce mortality, morbidity, and complications related to community-acquired pneumonia in patients who are immunocompetent and patients who are immunocompromised. These features include rapid diagnosis, microbiological investigation, prevention and management of complications (eg, respiratory failure, sepsis, and multiorgan failure), empirical antibiotic therapy in accordance with patient's risk factors and local microbiological epidemiology, individualised antibiotic therapy according to microbiological data, appropriate outcomes for therapeutic switch from parenteral to oral antibiotics, discharge planning, and long-term follow-up. This Seminar offers an updated view on community-acquired pneumonia in adults, with suggestions for clinical and translational research.